Hidden treasures - Britton,Fern (London: Harper, 2012)
Stephen O'Meara's new and exciting observing guide spotlights an original selection of 109 deep-sky objects that will appeal to sky-watchers worldwide. His 'hidden treasures' include a wonderful assortment of galaxies, open clusters, planetary nebulae and more, all of which have been carefully chosen based on their popularity and ease of observing. None of these objects are included in either the Messier or the Caldwell catalogs, and all are visible in a 4-inch telescope under dark skies. Stunning photographs and beautiful drawings accompany detailed visual descriptions of the objects, which include their rich histories and astrophysical significance. The author's original finder charts are designed to help observers get to their targets fast and efficiently.
Preface -- Acknowledgments -- 1. About this book -- 2. The hidden treasures -- Appendix A : Caroline Herschel : no ordinary eighteenth-century woman -- Appendix B : Hidden treasures : basic data -- Appendix C : Twenty additional hidden treasures -- Appendix D : Deep-sky lists : comparison table -- Appendix E : Photo credits -- Index -- The treasure chest.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Astronomy -- Charts, diagrams, etc; Electronic books